Increased Cortisol and Cortisone Levels in Overweight Children - Chu, Lanling (Med Sci Monit Basic Res, 2017)
BACKGROUND: It has been unclear whether relatively high cortisol and cortisone levels are related to overweight in childhood, parental body mass index (BMI), and family dietary habits. The aim of this study was to compare cortisol and cortisone levels in urine and saliva from overweight and normal children, as well as correlations between children’s BMI, parental BMI and family dietary behavior questionnaire score (QS). MATERIAL/METHODS: We analyzed the data from 52 overweight children and 53 age- and sex-matched normal-weight children aged 4–5 years. The concentrations of salivary cortisol (SF), salivary cortisone (SE), urinary cortisol (UF) and urinary cortisone (UE) were measured using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The family dietary behavior QS was answered by the parent mainly responsible for the family diet. RESULTS: Average cortisol and cortisone levels were significantly higher in overweight children. There was no significant difference in the ratio of cortisol to cortisone (R(cc)) and the marker of 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) activities. The results displayed correlations among cortisol, cortisone, and R(cc). Positive correlations were weak-to-moderate between BMI and SF, SE, UF, and UE. There were correlations between BMI and maternal BMI (mBMI), and BMI was significantly associated with QS. CONCLUSIONS: Our results suggest that cortisol and cortisone levels are associated with overweight in children, but the 11β-HSD2 activities showed no significant differences. Unhealthy family diet was associated with higher BMI, UF, and UE, and families with maternal overweight or obesity had a higher prevalence of children’s overweight or obesity.